Peran Asessment dan Evaluasi Pendidikan terhadap Akreditasi Sekolah - Nur Atika Alias; Lumanatul Latifah; Madona Agustin Sari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Accreditation is an important thing in an effort to obtain information about the real conditions of an educational institution based on minimum standards that have been set towards targeted educational planning. This research aims to determine the role of educational assessment and evaluation on school accreditation. The research method used is descriptive qualitative which describes in detail the topics discussed in this research. The research results illustrate several roles of educational assessment and evaluation in school accreditation, namely measuring the competencies of students, supporting improving teacher quality, as evidence of effective school management and supporting curriculum development. Apart from that, this research also discusses several points, namely the characteristics of educational assessment and evaluation, namely based on a comprehensive and holistic Islamic curriculum, continuous assessment (formative assessment), centered afterlife assessment, focus on spiritual development and worship, authentic and contextual assessment, oriented towards improvement and tazkiyah. Islamic education assessment and evaluation methods are competency-based assessment, authentic assessment, formative assessment, summative assessment and evaluation of worship practices. The educational assessment and evaluation approaches are the holistic approach, affective approach, spiritual approach and authentic approach.